2010
DOI: 10.1007/s11605-010-1244-5
|View full text |Cite
|
Sign up to set email alerts
|

Technique of Minimally Invasive Ivor Lewis Esophagogastrectomy with Intrathoracic Stapled Side-to-Side Anastomosis

Abstract: A 6-cm side-to-side stapled intrathoracic esophagogastric anastomosis is feasible and is associated with a low anastomotic leak rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Esophagectomy using the Ivor Lewis technique has been performed by many authors 26,27 . In this technique, esophagogastric anastomosis is carried out in the apex of the thorax and, besides preserving 5.0 cm more of esophagus compared to cervical anastomosis, is considered a radical surgical technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophagectomy using the Ivor Lewis technique has been performed by many authors 26,27 . In this technique, esophagogastric anastomosis is carried out in the apex of the thorax and, besides preserving 5.0 cm more of esophagus compared to cervical anastomosis, is considered a radical surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…Esophagectomy is a major surgery that has both a high morbidity rate (60%) and mortality rate, which may reach 26.7%, mainly due to pulmonary complications, cervical fistulas, stenosis of anastomosis, necrosis of the tubularized stomach, and mediastinitis 3-6 . Among these possible complications, fistulas of the esophagogastric anastomosis represent one of the main problems of esophagectomies. Incidence in several studies has ranged from 0% to 50%, with most authors reporting a high incidence of this complication 1,4,7,8 . Although these fistulas usually have a favorable course, about 2% of cases can have a catastrophic outcome 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, various MIS techniques have been reported in greater detail by others [12][13][14][15]. Although the reported technique for MIE varies, the frequency of this operation remains low nationally due to the technical difficulty of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid side-to-side anastomosis partially needs hand-sewn as well, and a 3-6 cm length of distal esophageal stump is required to create the extended anastomotic orifice, making this technique unsuitable for intrathoracic higher-level anastomosis [2,3]. To our knowledge, circular stapler is currently the primary approach with robot-assisted intrathoracic anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cadiere et al [1] reported that thoracoscopy in the prone position allowed the surgeon to perform a completely hand-sewn thoracoscopic esophagogastric anastomosis. Introduction of the thoracoscopic hybrid side-to-side anastomosis by extension of the posterior esophageal wall, using a linear stapler and anterior hand-sewn closure with 3.5-6 cm length extension, effectively prevented anastomotic stricture [2,3]. When a circular stapler was used to perform thoracoscopic esophagogastric anastomosis, the primary difficulty was with anvil placement in the esophageal lumen.…”
Section: Introductionmentioning
confidence: 99%